Intercultural willingness to communicate within health services: Investigating anxiety, uncertainty, ethnocentrism and help seeking behaviour. (September 2016) - Logan, Shanna; Steel, Zachary; Hunt, Caroline
Abstract: Anxiety Uncertainty Management (AUM) theory (Gudykunst, 2004) suggests that both anxiety and uncertainty are key factors that influence cross-cultural engagement within health services. The current study employed an experimental design to test AUM theory within a health context, specifically the impact of high or low perceived predictability and high or low anxiety on willingness to interact within a health care interaction. Additionally, the study assessed the unique contribution of state and trait anxiety, ethnocentrism and attitudes towards seeking psychological help, on participants' ratings of willingness to interact within a health setting to better understand health help-seeking behaviour. Results indicate that an anxiety provoking situation is a significant predictor of willingness to interact, with high anxiety leading to less willingness to interact, a finding enhanced when perceived predictability of a health professional was also low. This finding supports the application of AUM theory to the health setting. A heightened anxiety provoking situation was also found to have a direct effect on the perceived predictability of an intercultural health interaction partner. Despite previous research indicating the importance of help seeking behaviour and cultural attitudes in negatively influencing engagement with health services, the current study found that state anxiety was a more significant indicator of willingness to interact in a cross-cultural health interaction than these other indicators.